Monthly variations in aneurysmal subarachnoid hemorrhage incidence and mortality: Correlation with weather and pollution - Han, Myung-Hoon (PLoS One, 2017)
BACKGROUND AND PURPOSE: Although the effect of weather and air pollution on the occurrence of subarachnoid hemorrhage (SAH) has been investigated, results have remained inconsistent. The present study aimed to determine the seasonality of aneurysmal subarachnoid hemorrhage occurrence and mortality. METHODS: We used the National Inpatient Sample database to evaluate the effect of meteorological factors and air pollutants on patients with subarachnoid hemorrhage in Korea between 2011 and 2014. Monthly variations in SAH occurrence and mortality were analyzed using locally weighted scatter plot smoothing curves. Multivariate Poisson generalized linear regression models were used to evaluate potential independent meteorological and pollutant variables associated with SAH occurrence and mortality. RESULTS: In total, 21,407 patients who underwent clip or coil treatment owing to aneurysmal SAH in Korea from January 1, 2011, to December 31, 2014, were included. The crude incidence rate of SAH in Korea was 10.5 per 100,000 people per year. An approximately 0.5% lower risk of SAH was observed per 1°C increase in mean monthly temperature (relative risk, 0.995; 95% confidence interval [CI], 0.992–0.997; p < 0.001), while an approximately 2.3% higher risk of SAH was observed per 1°C increase in mean monthly diurnal temperature. CONCLUSIONS: We showed distinct patterns of seasonal and monthly variation in the occurrence and mortality of SAH. Our findings suggest that meteorological factors may play an important role in monthly variations in the occurrence of aneurysmal SAH.